Genes Involved in the Biosynthesis and Transport of Acinetobactin in - Tarik Hasan; Chul Hee Choi; Man Hwan Oh (Genomics & Informatics)
Pathogenic bacteria survive in iron-limited host environments by using several iron acquisition mechanisms. Acinetobacter baumannii, causing serious infections in compromised patients, produces an iron-chelating molecule, called acinetobactin, which is composed of equimolar quantities of 2,3-dihydroxybenzoic acid (DHBA), L-threonine, and N-hydroxyhistamine, to compete with host cells for iron. Genes that are involved in the production and transport of acinetobactin are clustered within the genome of A. baumannii. A recent study showed that entA, located outside of the acinetobactin gene cluster, plays important roles in the biosynthesis of the acinetobactin precursor DHBA and in bacterial pathogenesis. Therefore, understanding the genes that are associated with the biosynthesis and transport of acinetobactin in the bacterial genome is required. This review is intended to provide a general overview of the genes in the genome of A. baumannii that are required for acinetobactin biosynthesis and transport.